2002
DOI: 10.1161/01.res.0000043663.08689.05
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Ca 2+ Release, but Normal Ryanodine Receptors, in Canine and Human Heart Failure

Abstract: Sarcoplasmic reticulum (SR) Ca 2 transport proteins, especially ryanodine receptors (RyR) and their accessory protein FKBP12.6, have been implicated as major players in the pathogenesis of heart failure (HF), but their role remain controversial. We used the tachycardia-induced canine model of HF and human failing hearts to investigate the density and major functional properties of RyRs, SERCA2a, and phospholamban (PLB), the main proteins regulating SR Ca 2 transport. Intracellular Ca 2 is likely to play a role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
202
1
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(218 citation statements)
references
References 29 publications
12
202
1
3
Order By: Relevance
“…Even though circulating levels of catecholamines are constitutively higher than in healthy persons, beta-adrenergic receptors appear to be down-regulated, and the robust responsiveness to agents such as isoproterenol seen in healthy heart cells is severely attenuated (Marks, 2001;Chien et al, 2003). Biochemical studies have indicated that this abnormal, sustained "hyperadrenergic" state leads to excess phosphorylation of RyRs (Marx et al, 2000), although this result remains controversial (Jiang et al, 2002). Complementary planar lipid bilayer studies of RyR gating have predicted that this hyperphosphorylation will lead to increased RyR open probability.…”
Section: The Paradoxmentioning
confidence: 99%
“…Even though circulating levels of catecholamines are constitutively higher than in healthy persons, beta-adrenergic receptors appear to be down-regulated, and the robust responsiveness to agents such as isoproterenol seen in healthy heart cells is severely attenuated (Marks, 2001;Chien et al, 2003). Biochemical studies have indicated that this abnormal, sustained "hyperadrenergic" state leads to excess phosphorylation of RyRs (Marx et al, 2000), although this result remains controversial (Jiang et al, 2002). Complementary planar lipid bilayer studies of RyR gating have predicted that this hyperphosphorylation will lead to increased RyR open probability.…”
Section: The Paradoxmentioning
confidence: 99%
“…As attractive as this working hypothesis is, the attention it has received and its extensive testing by this group, it remains controversial. This is because numerous laboratory groups have found results that do not support different aspects of this hypothesis [1,[13][14][15][16][17]. These include findings that RyR2 is not hyperphosphorylated by PKA in HF, that PKA-dependent phosphorylation does not cause FKBP12.6 release, that PKA activation does not increase basal RyR2 activation, that there are additional PKA sites on RyR2 and that Ser-2809 can also be phosphorylated by CaMKII or PKG (protein kinase G).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, it has been proposed that increased protein kinase A (PKA)-mediated phosphorylation of RyR2 at serine 2808 (S2808) is an important signaling event in the development of heart failure (12,13). However, other studies in a canine model of heart failure disagreed with these findings (14). Genetic inactivation of RyR2-S2808 phosphorylation in S2808A knock-in mice was associated with normalized RyR2 activity and improved cardiac contractility following myocardial infarction (15).…”
mentioning
confidence: 99%